Biomimetic 3D-printed scaffolds for spinal cord injury repair - Koffler, Jacob (Nat Med, 2019)
Current methods for bioprinting functional tissue lack appropriate biofabrication techniques to build complex 3D microarchitectures essential for guiding cell growth and promoting tissue maturation(1). 3D printing of central nervous system (CNS) structures has not been accomplished, possibly owing to the complexity of CNS architecture. Here, we report the use of a microscale continuous projection printing method (μCPP) to create a complex CNS structure for regenerative medicine applications in the spinal cord. μCPP can print 3D biomimetic hydrogel scaffolds tailored to the dimensions of the rodent spinal cord in 1.6 s and is scalable to human spinal cord sizes and lesion geometries. We tested the ability of μCPP 3D-printed scaffolds loaded with neural progenitor cells (NPCs) to support axon regeneration and form new ‘neural relays’ across sites of complete spinal cord injury in vivo in rodents(1,2). We find that injured host axons regenerate into 3D biomimetic scaffolds and synapse onto NPCs implanted into the device and that implanted NPCs in turn extend axons out of the scaffold and into the host spinal cord below the injury to restore synaptic transmission and significantly improve functional outcomes. Thus, 3D biomimetic scaffolds offer a means of enhancing CNS regeneration through precision medicine.